Pengaruh Kelengkapan Produk, Kualitas Pelayanan, Dan Harga Terhadap Keputusan Pembelian Ulang Kebutuhan Rumah Tangga Di Sardo Swalayan Pada Mahasiswa Di Kota Malang - Rosa Intan Delavia; Rois Arifin; Satria Putra Utama (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study is to identify and assess how product completeness, service quality, and pricing affect consumers' choices to repurchase home goods at Sardo Swalayan. This study employed data from a study on students in the city of Malang, where the participants were chosen through purposive sampling and given questionnaires through the g-form. The Malhotra method was used to determine the sample size for this investigation, and 85 responses were the outcome. The analytical approach used in this study includes hypothesis testing (F test and t test), multiple linear regression analysis, classical assumption testing (multicollinearity test, heteroscedasticity test), instrument testing (validity test, reliability test), normality test, coefficient of determination test, and data processing using the IBM SPSS 22 program. According to the study's findings, product completeness partially does not affect repurchase decisions, service quality somewhat influences repurchase decision, and pricing partially affects repurchase decision. These factors all influence repurchase decisions simultaneously. Keywords : Product Completeness, Service Quality, Price, Repurchase Decision